Facebook text posts classification with TensorFlow - Druzhynin, О.О.; Nekhai, V.V.; Prila, O.A. (Математичні машини і системи, 2019)
Natural language processing (NLP) is one of the most important technologies of the XXI century. Machine Comprehension is a very interesting but challenging task in both Natural Language Processing (NLP) and artificial intelligent (AI) research. NLP can be applied wherever human-machine interaction is needed. Recently, deep learning methods show good results in tasks involving NLP. Standard models can often be used to solve a range of tasks, without the need to apply traditional analytical engineering techniques. The widespread distribution of social networks and the large number of users could give us impressive results, which can further build system interests analysis with a large number of established trust relationships. In this article, we will consider the task of classifying texts in relation to the object under study using the TensorFlow framework. Обробка природних мов (ОПМ) є однією з найважливіших технологій XXI століття. Машинне розуміння є дуже цікавим, але складним завданням як в обробці природних мов (ОПМ), так і в дослідженні штучного інтелекту (ШІ). ОПМ можна застосовувати там, де потрібна взаємодія людини з машиною (людино-машинна взаємодія). Останнім часом глибокі методи навчання показують вражаючі результати в вирішенні завдань, що стосуються ОПМ. Стандартні моделі глибокого навчання часто можуть використовуватися для вирішення цілого ряду завдань без необхідності застосування традиційних аналітичних інженерних методів, що потребують надзвичайно багато ресурсів. У цій статті ми розглянемо завдання класифікації текстів по відношенню до досліджуваного об'єкта за допомогою фреймворка «TensorFlow».
Remove selected Обработка естественных языков (ОЕЯ) является одной из важнейших технологий XXI века. Машинное понимание очень интересное, но сложное задание как в обработке естественных языков (ОЕЯ), так и в исследовании искусственного интеллекта (ИИ). ОЕЯ можно применять там, где требуется взаимодействие человека с машиной (человеко-компьютерное взаимодействие). В последнее время глубокие методы обучения показывают впечатляющие результаты в решении задач, касающихся ОЕЯ. Стандартные модели глубокого обучения часто могут использоваться для решения целого ряда задач, без необходимости применения традиционных аналитических инженерных методов, требующих очень много ресурсов. В этой статье мы рассмотрим задачи классификации текстов по отношению к исследуемому объекту с помощью фреймворка «TensorFlow».